Reproducibility of Left Ventricular Dyssynchrony Indices by Three-Dimensional Speckle-Tracking Echocardiography: The Impact of Sub-optimal Image Quality - Al Saikhan, Lamia; Park, Chloe; Hughes, Alun D. (Frontiers in Cardiovascular Medicine, 2019)
Background: 3D speckle-tracking echocardiography (3D-STE) is a novel method to quantify left ventricular (LV) mechanical dyssynchrony. 3D-STE is influenced by image quality, but studies on the magnitude of its effect on 3D-STE derived LV systolic dyssynchrony indices (SDIs) and their test-retest reproducibility are limited. Methods: 3D-STE was performed in two groups, each comprising 18 healthy volunteers with good echocardiographic windows. In study 1, optimal and inferior-quality images, by intentionally poor echocardiographic technique, were acquired. In study 2, sub-optimal quality images were acquired by impairing ultrasound propagation using neoprene rubber sheets (thickness 2, 3 and 4 mm) mimicking mildly, moderately and severely impaired images respectively. Measures (normalized to cardiac cycle duration) were volume- and strain-based SDIs defined as the standard deviation of time to minimum segmental values, and volume- and strain-derived dispersion indices. For both studies test-retest reproducibility was assessed. Results: Test-retest reproducibility was better for most indices when restricting the analysis to good quality images; nevertheless, only volume-, circumferential strain- and principal tangential strain-derived LV dyssynchrony indices achieved fair to good reliability. There was no evidence of systematic bias due to sub-optimal quality image. Volume-, circumferential strain- and principal tangential strain-derived SDIs correlated closely. Radial strain- and longitudinal strain-SDI correlated moderately or weakly with volume-SDI respectively. Conclusions: Sub-optimal image quality compromised the reliability of 3D-STE derived dyssynchrony indices but did not introduce systematic bias. Even with optimal quality images, only 3D-STE indices based on volume, circumferential strain and principal tangential strain showed acceptable test-retest reliability.